Ethnoichthyology and Ethnotaxonomy of the Kichwa Indigenous People of Arawanu (Arajuno), in the Ecuadorian Amazon - Tobes, Ibon; Carrillo-Moreno, Carolina; Guarderas-Flores, Lida; Jácome-Negrete, Iván; Velázquez-Cárdenas, Yetlanezi (Frontiers in Ecology and Evolution, 2022)
The Amazon Basin is home to a great number of Indigenous nationalities that have coevolved with aquatic habitats and fish resulting in a precise traditional ecological knowledge. Nevertheless, this biocultural heritage is threatened by the degradation of rivers and fisheries and cultural erosion. This research was designed and carried out in the community of Arawanu (Arajuno in Spanish), in the Ecuadorian Amazon, and was requested by the local Kichwa people looking for guidance to gather, systematize and disseminate their ethnoichtyological knowledge. Data collection was carried out through participatory workshops using the pile sorting technique in group dynamics, to identify, name and classify local fish and compile biocultural information about them. From the Linnaean taxonomic perspective, 86 taxa were identified, included in 26 families, and corresponded with 16 Kichwa ethnofamilies and 58 ethnospecies. Five classification levels were identified: I) Aycha: unique beginner - Animalia kingdom; II) Yaku Aycha: life form - Pisces superclass; III) Ayllukuna: ehtnofamilies - Linnaean families; IV) Ethnogenera - Linnaean genus and V) Ethnospecies - Linnaean species. A one-to-one correspondence was registered between 35 Kichwa ethnospecies and Linnean species, along with one case of over-differentiation and 21 cases of subdifferentiation (Type A: 7; Type B: 14). The Kichwa ethnoichthyological classification is multidimensional and considers attributes like skin and scales, fishbones and spines, meat quality, body shape, diet and salience. Of the 58 ethnospecies, 38 were valued for consumption, while medicinal and spiritual uses were mentioned for 40 of them. The participatory work created a forum to discuss the value and threats to ichthyofauna and freshwater systems, enabled the dissemination of their biocultural heritage, and highlighted the cultural relevance of hydro-social ecosystems in their livelihood. The collected information may be critical to adapt local education systems to the Kichwa worldview and to pass down traditional ecological knowledge to future generations, fostering a respectful, careful and conscious relationship between humans and nature. Our results offer a solid and novel information compilation and practical guidance for participatory ethnobiological surveys. Additionally, the ethnobiological and the ethnotaxonomical information establishes the basis to develop sustainable fishing strategies and promote conservation of the local ichthyofauna.